A MODEL OF THE STATICALLY INDETERMINATE TENSION IN THE BLADE OF A HORIZONTAL BANDSAW (Innovation in Woodworking Industry and Engineering design, 2026)
An original model is proposed for determination of the statically indeterminate tension (internal tensile force) in the blade (saw band) of a horizontal bandsaw with a tensioning spring mechanism. The statically indeterminate problem is solved in a way missing in the bandsaw references but required by the Strength of Materials science: based on a deformation compatibility equation. In the case considered, in that equation the spring parameters are also involved. The model proposed is a generalization of a published previous model (Stefanov 2013) regarding a vertical bandsaw blade tension.